Al-doping induced superior lithium ion storage capability of LiNiO2 spheres. Issue 12 (15th August 2020) - Cao, Haishang; Du, Fanghui; Adkins, Jason; Zhou, Qun; Dai, Hui; Sun, Pengpeng; Hu, Die; Zheng, Junwei
Abstract: To optimize the performance of LiNiO2 with minimal modification of the pristine structure, a facile solid-state approach, based on the interdiffusion of elements at the solid/solid interface, is developed to achieve uniformly Al-doped LiNiO2 using alumina coated Ni(OH)2 spheres as the precursor. The resulting LiNi0.95 Al0.05 O2 material exhibits excellent discharge capacity (209.9 mAh g −1 at 0.1 C) and cycling stability with a capacity retention of 85.10% after 200 cycles at 0.5 C. This is ascribed to the improved reversibility of the phase transitions by Al-doping as revealed by in-situ XRD characterization. The Al-doping also endows the material with superior rate capability due to the enlarged interlayer spacing in the structure and alleviation of the side reactions at the electrode/electrolyte interface, favorable for lithium ion diffusion. An optimal amount of doped Al is necessary for ensuring the structure stability and interface ionic conductivity of the LiNiO2 spheres. Thus, the present strategy may provide an opportunity to optimize the performance of LiNiO2, with uniform doping of a small amount of Al, producing a promising cathode material for advanced lithium ion batteries.